Astrocytes profiling in acute hepatic encephalopathy: Possible enrolling of glial fibrillary acidic protein, tumor necrosis factor-alpha, inwardly rectifying potassium channel (Kir 4.1) and aquaporin-4 in rat cerebral cortex - Elsherbini, Dalia Mahmoud Abdelmonem; Ghoneim, Fatma M.; El-Mancy, Eman Mohammed; Ebrahim, Hasnaa Ali; El-Sherbiny, Mohamed; El-Shafey, Mohamed; Al-Serwi, Rasha Hamed; Elsherbiny, Nehal M. (Frontiers in Cellular Neuroscience, 2022)
Hepatic encephalopathy (HE) is a neurological disarray manifested as a sequel to chronic and acute liver failure (ALF). A potentially fatal consequence of ALF is brain edema with concomitant astrocyte enlargement. This study aims to outline the role of astrocytes in acute HE and shed light on the most critical mechanisms driving this role. Rats were allocated into two groups. Group 1, the control group, received the vehicle. Group 2, the TAA group, received TAA (300 mg/kg) for 3 days. Serum AST, ALT, and ammonia were determined. Liver and cerebral cortical sections were processed for hematoxylin and eosin staining. Additionally, mRNA expression and immunohistochemical staining of cortical GFAP, TNFα, Kir4.1, and AQP4 were performed. Cortical sections from the TAA group demonstrated neuropil vacuolation and astrocytes enlargement with focal gliosis. GFAP, TNFα, and AQP4 revealed increased mRNA expression, positive immunoreactivity, and a positive correlation to brain water content. In contrast, Kir 4.1 showed decreased mRNA expression and immunoreactivity and a negative correlation to brain water content. In conclusion, our findings revealed altered levels of TNFα, Kir 4.1, GFAP, and AQP4 in HE-associated brain edema. A more significant dysregulation of Kir 4.1 and TNFα was observed compared to AQP4 and GFAP.